Changes in Sensory, Physicochemical and Microbiological Properties of Ronto During Fermentation - Khairina, Rita; Utami, Tyas; Raharjo, Sri; Cahyanto, Muhammad Nur (Pakistan Journal of Nutrition, 2017)
Background and Objective: Ronto is a traditional Indonesian fermented shrimp product; however, there are very few reports on how its properties change during fermentation. The aim of this study was to study the changes in sensory, physicochemical and microbiological properties of ronto during fermentation. Materials and Methods: Shrimp (Acetes japonicus) was mixed with salt and rice to give a mixture that was 11.5% salt and 20% rice. The mixture was put into plastic bottles and incubated at room temperature for 18 days. Samples were taken after every 2 days and sensory, physicochemical and microbiological properties were analyzed. Results: It was found that the fermented shrimp developed a sour, savory flavor and bright pink color after 8 days of fermentation, both of which became stronger after 12 days. After 14 days of fermentation, the texture of the shrimp gradually became that of a porridge-like paste. The acidity of the fermented shrimp increased during fermentation, after 12 days of fermentation, the pH had decreased from 8.3-4.8. The total volatile bases increased from 25-150 mg N/100 g over 18 days of fermentation. Lactic acid, proteolytic and amylolytic bacteria were involved in the fermentation process. The concentrations of these three bacteria increased during the early phases of fermentation and decreased in the later phases. Conclusion: Ronto fermentation ended after 14 days when the color of the fermented material became bright pink and when it had developed a strong, sour and savory flavor. That product had a lightness (53.11), a redness (11.72), a yellowness (15.68), a pH (4.8) and the texture of porridge-like paste and was relatively low in total volatile bases.